Examining the efficacy for an athlete centered, coach driven, sport science based model in Canada: Lessons on leadership and sport science learned at the National Sport Centre Manitoba - Gannon, G. A. (2001)
Since the recent establishment of the various National Sport Centres in Canada, the ability of sport scientists to deliver the knowledge of their respective disciplines has grown. Specifically, a performance enhancement team (PET) was established at the National Sport Centre - Manitoba as a result of the ideas and systems instituted at the National Sport Centre in Calgary (Smith & Norris, 2000) and other sport systems based around the world (of most relevance are the systems of Norway and Australia). This multi-disciplinary focus is becoming critical in many professional settings (Corrigan, Lickey, Campion & Rashid, 2000) and will be important in order to maximize the potential for international success for Canada's elite athletes and teams. Of significance is the emerging reality that the role of our National Team / Training Centre Head Coaches is changing. Effective coaching leadership is now more positively related to a coach's ability to collaborate and to share decision-making in appropriate areas with both their 'professional team" and their athletes (Werthner, 2001). Moreover, it is imperative that the collaborative efforts of sport science team members be integrated into the internal environment in an expeditious manner, as any delay can result in a substantial decrease in the potential success of the athlete. Clearly, coaches must have the knowledge and ability to effectively facilitate different leadership roles within the group, than simply pursue traditional leadership approaches that comprised much of the coaching profession in the past (Limerick, Cunnington and Crowther, 1998). Although there are many positive aspects to this "coaching team" approach, there are also many issues that must be fully appreciated and understood. The purpose of this presentation is to examine the efficacy for an athlete centered, coach driven, sport science based model of athlete development and to discuss the various lessons that have been learned by the Performance Enhancement Team at the National Sport Centre - Manitoba. Specifically, the "team" will draw from the knowledge they have attained as a result of their work with the Manitoba National Triathlon Centre.